Aerobic fitness and game performance indicators in professional football players; playing position specifics and associations - Modric, T.; Versic, S.; Sekulic, D. (Heliyon, 2020)
The aim of this study was to identify associations between aerobic fitness (AF) and game performance indicator (GPI) in elite football. Participants were professional football players (males, n = 16; age: 23.76 ± 2.64; body height: 181.62 ± 7.09 cm; body mass: 77.01 ± 6.34 kg). AF testing was conducted by direct measurement and included VO2max, running speed at aerobic threshold (AeT), and running speed at anaerobic threshold (AT). The GPI were collected by the position-specific performance statistics index (InStat index). The players were observed over one competitive half-season, resulting in 82 game performances, grouped according to the positions in game: defenders (n = 39), midfielders (n = 32) and forwards (n = 11). VO2max was not found to be a good discriminator of AF among different playing positions. AeT (F-test = 26.36. p = 0.01) and AT (F-test = 7.25, p = 0.01) were highest among midfielders, and lowest among forwards. No correlations were found between AF and GPI. This study confirmed that AeT and AT are better indicators of AF than VO2max in football players at different playing positions. The lack of associations between AF and GPI was discussed with regard to calculation of InStat as a GPI.